2019
DOI: 10.5624/isd.2019.49.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral and maxillofacial swellings using ultrasonographic features

Abstract: PurposeThe aim of this study was to evaluate the characteristic features of oral and maxillofacial swellings that could be seen on ultrasonographic examinations.Materials and MethodsFifty patients with oral and/or maxillofacial swellings were randomly selected, thorough case histories and clinical examinations were done, ultrasonographic examinations with Doppler imaging were performed, and the features of every group were studied. Finally, histopathological evaluations were performed to identify the final dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…They showed the reliability of USG to be 97% in diagnosing all the cases when compared to histopathological or clinical diagnosis. The present study was also found to be analogous to the studies conducted by Abdelsalam TA et al (2019) 20 and Adamu YM et al (2022). 21 In this study ultrasonographic picture of the abscess was hypoechoic, homogenous or heterogenous because of its pus or inflammatory exudate content and the findings were consistent with the findings of Srinivas K et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…They showed the reliability of USG to be 97% in diagnosing all the cases when compared to histopathological or clinical diagnosis. The present study was also found to be analogous to the studies conducted by Abdelsalam TA et al (2019) 20 and Adamu YM et al (2022). 21 In this study ultrasonographic picture of the abscess was hypoechoic, homogenous or heterogenous because of its pus or inflammatory exudate content and the findings were consistent with the findings of Srinivas K et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…These results were in near approximation to previous studies[ 4 , 5 , 18 , 19 ]. One previous study showed a significant association between histological findings and ultrasonography of oral maxillofacial swelling[ 20 ]. USG is inexpensive, fast, more available, and has less risk of radiation exposure to patients[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, US can be used to identify intraosseous lesions, such as periapical lesions, and provide valuable information on blood flow direction using Doppler technology. Combining these features, US contributes significantly to precise lesion diagnosis and aids in developing appropriate treatment plans [5,22,23]. US does not present the same risks as radiological evaluations and can be successfully used in dentistry and oral surgery to image periapical bone defects and lesions [20,24].…”
Section: Introductionmentioning
confidence: 99%